POV Instagram sebagai Media Promosi: Literasi Digital Generasi Z terhadap Konten Edukatif - Wulandari, Gusti Ayu Mia Cendhana; Permatasari, Ni Putu Intan (IAI Nasional Laa Roiba Bogor, 2025)
Social media, particularly Instagram, has become a vital platform for promoting and educating about local products in the digital era, especially among Generation Z. This study aims to analyze the role of Instagram as an educational promotional media in enhancing digital literacy among Generation Z in the context of Bali Alus products. The research employs a qualitative case study approach, collecting data through observation of @balialus.id Instagram account, in-depth interviews with managers and audiences, and document analysis of content and digital literacy frameworks. Data analysis is based on Belshaw’s (2011) digital literacy framework and the four digital capability dimensions described by Trisna and Batubara (2025), including technical, cognitive, social, and ethical aspects. Findings indicate that Bali Alus’ engaging, cinematic, and visual content effectively increases Generation Z’s understanding and appreciation of Bali’s natural products, fostering positive brand perception through edutainment approaches. Short videos and humor-based content significantly enhance engagement and awareness of Bali’s cultural richness, as well as improving digital literacy levels. The discussion highlights the importance of adaptive, creative, and ethical digital communication strategies in optimizing Instagram’s potential as an educational and promotional platform for local products, tailored to the characteristics of Generation Z.